Production and Nutritional Quality of High Yielding Fodders in the Coastal Areas for Ruminants (The Agriculturists, 2016)
The experiment was conducted to study the production and nutritional values of high yielding fodders by the goat farmers in Kobirhat and Subornochar upazilas of Noakhali District. The yields of high yielding forages had significant differences among the species. The average higher biomass were obtained from Napierhybrid (34), Napier-aerosa (20), Napierbazra (17.33) and Splendida (19). The Andropogon and Signal fodder had similar yields of 12.67 & 13.67 t/ha/cut. There was a significant (P